Analysis of School Principal Tasks (Study at SMP Muhammadiyah PK Kota Barat Surakarta and SMP IT Al Anis Kartasura) - Rima Aritaningsih; Bambang Sumardjoko; Muthoifin Muthoifin (Edumaspul: Jurnal Pendidikan, 2023)
Education system policy that gives authority to leaders is expected to make it easier for school principals to carry out their duties in achieving educational success. The study aims to analyze the characteristics of the principal’s duties as manager, supervisor and entrepreneur in SMP Muhammadiyah PK Kota Barat Surakarta and SMP IT Al Anis Kartasura. This type of research is field research, it uses data collection techniques, in depth interviews, observation and documentation. This research is a qualitative descriptive study with case study approach. The results of the study reveal the characteristics of the principal’s duties as a manager that the principals manage the school program including a time framed work plan for the management of curriculum. The characteristics of the principal’s duties as supervisors are indicated by the principals planning supervision activities by forming a team, carrying out academic supervision with class visits and carry out follow up supervision by including training. The characteristics of the principal’s duties as an entrepreneur can be seen from the school programs innovations such as curriculum development, motivating school stakeholders through advice on instilling an entrepreneurial spirit through a culture of habituation.